Incidence of trekking in the local economy. An empirical analysis to purpose of the Parque Natural Sierra de las Nieves (Málaga) - Ocaña Ocaña, Carmen; Larrubia Vargas, Remedios; Navarro Rodríguez, Susana (Anales de Geografía de la Universidad Complutense, 2013)
The article analyzes trekking in the P. N. Sierra de las Nieves, as a productive tourist activity, using a survey of its users. After a characterization of the study area, the work is aimed at establishing first the walkers’ consumption profile. It is analyzed their social characters (age, sex, social status), and the way they practice trekking inside the park (routes, duration, consumption). Then, the amount of expenses incurred in the place is calculated, as an objective reference the likely revenue stream for the local society.